The erbium ions absolute concentration measuring technique in active fiber preform - Latkin, K.P.; Smirnov, A.S.; Konstantinov, Yu.A.; Burdin, V.V. (Perm Federal Research Centre Journal, 2018)
Active optical fibers are used as an active medium in optical fiber amplifiers and lasers. The concentration of the active impurity in the core of the fiber is their main characteristic which determines the main parameters of future lasers and amplifiers. The paper proposes the active impurity absolute concentration measuring technique in active fiber perform of an active optical fiber. The technique is based on measuring the luminescence intensity of the active impurity. The technique is considered on the example of an erbium-doped preform. The luminescence exciting radiation has a wavelength of 980 nm and is directed along the axis of the preform. The luminescence is observed in the spectral region of 1.50 - 1.55 μm. The luminescence intensity is recorded from the side surface of the preform. The paper presents a working formula for calculating the absolute value of the concentration of the active element, in particular, erbium ions. The evaluation of the sensitivity of the technique to various concentrations of the active additive is given. The paper also provides some considerations of the technique sensitivity to the stability of the radiation source. These measurements allow us to analyze and control the production process of active optical fibers preforms, to forecast the active impurity concentration and its homogeneity along the fiber produced from the studied perform